2020
DOI: 10.3389/fmicb.2020.593006
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Metatranscriptomic Analyses Revealed Uncultured Bacteroidales Populations as the Dominant Proteolytic Amino Acid Degraders in Anaerobic Digesters

Abstract: Current understanding of amino acid (AA) degraders in anaerobic digesters is mainly based on cultured species, whereas microorganisms that play important roles in a complex microbial community remain poorly characterized. This study investigated short-term enrichments degrading single AAs using metagenomics and metatranscriptomics. Metagenomic analysis revealed that populations related to cultured AA degraders had an abundance <2.5% of the sequences. In contrast, metagenomic-assembled bins related to unculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 68 publications
(85 reference statements)
2
26
0
Order By: Relevance
“…Hydrogenase activity can be predicted based on primary sequence ( Søndergaard et al, 2016 ). The HydDB database has been widely utilized to classify hydrogenases ( Dong, 2020 ; Mei, 2020 ; Panwar, 2020 ; Park et al, 2020 ; Picone et al, 2020 ; Stairs et al, 2020 ; Wong, 2020 ; Yu et al, 2020 ). We confirmed the reliability of gene annotations in the HydDB database using a simulated metagenomic dataset of hydrogenase-containing and hydrogenase-free genomes (see Materials and methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogenase activity can be predicted based on primary sequence ( Søndergaard et al, 2016 ). The HydDB database has been widely utilized to classify hydrogenases ( Dong, 2020 ; Mei, 2020 ; Panwar, 2020 ; Park et al, 2020 ; Picone et al, 2020 ; Stairs et al, 2020 ; Wong, 2020 ; Yu et al, 2020 ). We confirmed the reliability of gene annotations in the HydDB database using a simulated metagenomic dataset of hydrogenase-containing and hydrogenase-free genomes (see Materials and methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…In general, metaproteomic analysis of front-end processes appears to be challenged by information overload in highly complex systems, which may benefit from statistical reduction of meta-data. In contrast to metaproteomics, metatranscriptomics is identity focused, and allows ready highlighting of metabolically active (amino acid) organisms (Mei et al, 2020) with more complex function being difficult to determine.…”
Section: Meta-omics Applied To Anaerobic Digestersmentioning
confidence: 99%
“…For example, Clostridium , Sedimentibacter , Peptoclostridium , and so on. were reported to metabolize various AAs. In this study, the metabolic proteins in main bacteria are shown in Table S2 (Supporting Information). The key enzymes involved in glutamate biotransformation to VFAs included glutamate dehydrogenase, glutamate mutase, methylaspartate ammonia-lyase, pyruvate: flavodoxin/ferredoxin oxidoreductase, phosphate acetyltransferase, glutamate racemase (Murl), acetate kinase, and butyrate kinase being expressed in Clostridium .…”
Section: Resultsmentioning
confidence: 99%